Pembatalan Perkawinan Disebabkan Orientasi Seksual Terhadap Sesama Jenis Ditinjau Dari Undang-Undang Perkawinan Dan Kompilasi Hukum Islam (Studi Kasus Terhadap Putusan Pengadilan Agama Bantul Nomor 72/Pdt.G/2021/Pa.Btl) - Priscila Rotua Caroline Br Panjaitan; Renny Supriyatni; Artaji Artaji (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Marriage is a sacred bond between a man and a woman to build a happy and eternal household. Legal marriages are carried out based on the provisions stipulated in laws and regulations, namely the Religious Law of each party and Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage. Marriages that do not fulfill or violate these provisions can be annulled by applying for an annulment of marriage, such as the case in the Bantul Religious Court Decision Number 72/Pdt.G/2021/PA.Btl. The petitioner is a wife who filed for annulment of her marriage because her husband likes the same sex.The purpose of this study is to find out and analyze the judge's considerations regarding the reasons used by the Petitioner and the legal consequences of the judge's decision granting the request for annulment of the marriage.This research is a normative juridical research with secondary data through library research accompanied by the results of interviews which are only as supporting data. The results of the study found that the judge's consideration regarding the reasons put forward by the Petitioner was by the provisions in the statutory regulations. The judge considered that the reason the Petitioner filed an annulment request against her husband who liked the same sex was a misunderstanding of the husband because the Petitioner only found out about this after the marriage was implemented. The legal consequences of the decision granted by the judge regarding the annulment of a marriage do not apply retroactively to children, joint assets, and third parties.